High-precision, underground visualisation for infrastructure works. (Research'eu results magazine)
Utility field work can be a real headache even with precise maps at hand. Admitting that they rapidly manage to locate the sought network, workers may end up damaging grids belonging to someone else. This type of scenario will soon be avoidable thanks to an assistive device developed under the LARA project.